Study of Furoxan Derivatives for Energetic Applications. Issue 4 (28th January 2013) - Li, Yanan; Zhang, Zhizhong; Ge, Zhongxue; Wang, Bozhou; Lai, Weipeng; Luo, Yifen
Abstract Two novel energetic compounds, 3, 4‐bis(1′, 2′, 4′‐triazole‐3′‐yl)furoxan (BTAF) and 3, 4‐bis(1′‐nitro‐1′, 2′, 4′‐triazole‐3′‐yl)furoxan (BNTAF), were prepared and their structures were characterized by IR, 1H NMR, 13C NMR, MS techniques and elemental analysis. The properties of BTAF and BNTAF were estimated. The predicted performance data of BTAF are as follows: density (measured) is 1.75 g/cm3, nitrogen content 50.9%, detonation velocity 7277 m/s, detonation pressure 20.1 GPa and enthalpy of formation +419.7 kJ/mol. The predicted performance data of BNTAF are as follows: density is 1.84 g/cm3, nitrogen content 45.2%, enthalpy of formation +841.5 kJ/mol, detonation velocity 8490 m/s and detonation pressure 32.4 GPa. The main themal properties of BTAF and BNTAF were analyzed by DSC and TG techniques, the results show that BTAF melts with concomitant decomposition at 188.8°C, the melting point of BNTAF is at 99.2°C and its first decomposition temperature is 139.2°C.